“Jo Kawin Bocah” Social Movement to Reduce Child Marriage Rates in Central Java - Arafah, Nawal Nur; Purwanto, Purwanto (Faculty of Social and Political Sciences - UIN Walisongo Semarang, 2023)
The “Jo Kawin Bocah” (Javanese term for “No Child Marriage”) movement implemented by the Central Java Government over the past two years has significantly reduced the number of child marriages in Central Java province. This research aims to analyze the concept of “Jo Kawin Bocah” as a government-sponsored movement, identify the critical success factors, and explore the concept in terms maqāṣid al-sharī'ah (Sharia objectives). This field research uses a qualitative approach and deductive thinking, with data collected from interviews and documentation. The findings show that the social movement is feasible because stakeholders are aware of the negative impacts of early marriage. Another critical success factor is the involvement of community members and district/city leaders and collaboration between civil society organizations, the government, educational institutions, and other cross-sector organizations. Viewed from the maqāṣid al-sharī'ah side, the social movement “Jo Kawin Bocah” can realize the protection of the soul (ḥifẓ al-nafs), protection of the mind (ḥifẓ al-‘aql), protection of assets (ḥifẓ al-māl), and protection of offspring (ḥifẓ al-nasl). This research implies that increasing awareness about the negative consequences of early marriage is the key to the success of social movements.